Reproduksi Budaya Patriarki dalam Komentar Netizen Terhadap Kasus Pembunuhan Tiara di Media Sosial TikTok - Kenia Tsabita Ramadhanti; Nuriyatul Lailiyah (Jurusan Ilmu Komunikasi, FISIP, Universitas Diponegoro, 2026)
The Reproduction of Patriarchal Culture in Netizens' Comments on Tiara's Case on TikTok. Violence against women remains a persistent issue in Indonesia. One case that attracted public attention was the murder of Tiara by her partner, Alvi, which was widely discussed on TikTok. Responses from TikTok users revealed tendencies toward victim blaming and justification of the perpetrator, indicating the reproduction of patriarchal culture in digital spaces. This study aims to identify the representation of female victims and male perpetrators and to analyze the reproduction of patriarchal culture in users' responses to Tiara's murder case. The study employed a descriptive qualitative approach using Sara Mills' Critical Discourse Analysis. Data were collected through documentation of TikTok users' responses and analyzed using the concepts of subject-object position and reader position. The findings show that the female victim was represented as partly responsible for the violence she experienced, while the male perpetrator was represented as someone whose actions could be understood or justified. Patriarchal culture was reproduced through victim blaming, moral surveillance of women, moral legitimization of the perpetrator, and the normalization of male aggression.